Meningkatkan Prestasi Belajar Siswa dalam Menyelesaikan Soal Bilangan Cacah Besar dengan Teknik Pembelajaran Kooperatif Tipe Teams Games Tournament pada Siswa Kelas IV SDK Ruto - Agustina Fono (Publikasi Indonesia, 2025)
Education in the era of globalization faces various challenges, such as curriculum changes and technological advancements, which require educational institutions to continually innovate. The quality of education is greatly influenced by effective communication between teachers and students, as well as the selection of appropriate teaching methods. This study aims to analyze the implementation of the cooperative learning model, specifically the TGT (Teams Games Tournament) type, in improving the learning achievements of 4th-grade students at SDK Ruto in solving large whole number problems. The method used is Classroom Action Research (CAR), consisting of three cycles, each involving planning, implementation, observation, analysis of learning outcomes, and reflection. The research subjects were 13 4th-grade students in the 2024/2025 academic year. The results of the study indicate that the application of the TGT model can enhance students' learning outcomes. The class average increased from 55.6 on the pre-test to 86.72 in the third cycle, and the percentage of students achieving mastery increased from 53.8% to 100%. Challenges in group formation and lack of cooperation among group members were addressed by having the teacher form the groups and appointing a group leader. This study suggests that the TGT model should be applied in Mathematics instruction to improve students' ability to solve large whole number problems.